Cross-Cultural Management : Essential Concepts - Thomas, David C. (SAGE Publications, Inc. (US), 2016)
Cross-Cultural Management: Essential Concepts, Fourth Edition introduces readers to the fundamentals of cross-cultural management by exploring the influence of culture on interpersonal interactions in organizational settings and examining the ever-increasing number of cross-cultural management challenges that global managers face in today’s workplace. Instead of taking a country specific approach, authors David C. Thomas and Mark F. Peterson offer a predominantly psychological perspective—focusing on the interactions of people from different cultures in organizational settings. This approach shows readers the effects culture has on a wide variety of cross-cultural interactions across organizational contexts.